Inside the Japanese company - Graham, Fiona (New York : RoutledgeCurzon, 2003)
"In this ethnographical study of a major Japanese white-collar company, the author explores the attitudes of Japanese employees towards their work, their company, and to related issues." "Based on extensive original research inside a Japanese insurance company (C-Life), which subsequently went bankrupt, the book shows that attitudes towards life-time employment, company loyalty and the other characteristics of Japanese working life, which are often portrayed in stereotype form in the West are, in fact, more complicated than is at first apparent."--BOOK JACKET.
1. Introduction -- 2. Literature review -- 3. The company and structure -- 4. The company and career -- 5. The company and life -- 6. The company and human relations -- 7. Ideology, groupism and individualism.
Includes bibliographical references and index.
Keywords: Life insurance -- Japan -- Management; Industrial relations -- Japan; National characteristics, Japanese